PENTINGNYA KEPUASAN PELANGGAN BAGI TRAVEL HAJI DAN UMROH DI BANJARMASIN - Noviyanti, Devi (UIN Antasari Banjarmasin, 2017)
The customerâs satisfaction should be the priority of hajj and umroh travel agency in high competition, especially in Banjarmasin. The customerâs satisfaction is a ratio between prospects and performance. It is very meaningful to the company. The company can measure the satisfaction rate using many strategies for the on going improvement of company management